Salmonella Evades d-Amino Acid Oxidase To Promote Infection in Neutrophils - Brian R. Tuinema (American Society for Microbiology, 2014)
ABSTRACT Neutrophils engulf and kill bacteria using oxidative and nonoxidative mechanisms. Despite robust antimicrobial activity, neutrophils are impaired in directing Salmonella clearance and harbor viable intracellular bacteria during early stages of infection that can subsequently escape to more-permissive cell types. The mechanisms accounting for this immune impairment are not understood. We report that Salmonella limits exposure to oxidative damage elicited by d-amino acid oxidase (DAO) in neutrophils by expressing an ABC importer specific for d-alanine, a DAO substrate found in peptidoglycan stem peptides. A Salmonella dalS mutant defective for d-alanine import was more susceptible to killing by DAO through exposure to greater oxidative stress during infection. This fitness defect was reversed by selective depletion of neutrophils or by inhibition of DAO in vivo with a small-molecule inhibitor. DalS-mediated subversion of neutrophil DAO is a novel host-pathogen interaction that enhances Salmonella survival during systemic infection. IMPORTANCE Neutrophils engulf Salmonella during early stages of infection, but bacterial killing is incomplete. Very little is known about how Salmonella survives in neutrophils to gain access to other cell types during infection. In this study, we show that d-amino acid oxidase (DAO) in neutrophils consumes d-alanine and that importing this substrate protects Salmonella from oxidative killing by neutrophil DAO. Loss of this importer results in increased bacterial killing in vitro, in neutrophils, and in a mouse model of infection, all phenotypes that are lost upon inhibition of DAO. These findings add mechanistic insight into a novel host-pathogen interaction that has consequences on infection outcome.